A longitudinal cross-sectional analysis of substance use treatment trends for individuals experiencing homelessness, criminal justice involvement, both, or neither - United States, 2006-2018 - Riley D. Shearer; Nathan D. Shippee; Kathrine Diaz Vickery; Maria A. Stevens; Tyler N.A. Winkelman (Elsevier, 2022)
Summary: Background: Individuals experiencing homelessness or criminal justice involvement (CJI) have higher rates of substance use than the general public. Despite documented barriers to accessing treatment, few studies have compared substance use treatment patterns between these groups. Methods: This paper uses data from the Treatment Episode Dataset-Admissions between 2006 to 2018 to describe characteristics and trends in substance use treatment admissions indicating homelessness (n=2,524,413), CJI (4,764,750), both (509,902), or neither (8,950,797) in the United States. We used multivariable logistic regression to examine trends independent of demographic differences between groups. Findings: Between 2006 and 2018, the proportion of treatment admissions related to heroin increased across all groups. Methamphetamine-related admissions rose substantially for individuals experiencing homelessness, CJI, or both. By 2018, 27·8% (95% CI: 27·4-28·2%) of admissions for individuals experiencing both were methamphetamine-related and 16·7% (95% CI: 16·3-17·0%) were heroin-related. Conversely, among individuals experiencing neither, 7·5% (95% CI: 7·4-7·5%) of admissions were methamphetamine-related and 33·6% (95% CI: 33·4-33·7%) were heroin-related. Individuals experiencing both homelessness and CJI received lower rates of medications for opioid use disorder (OUD) (8·3%; 95% CI: 8·2-8·3%) compared to individuals experiencing neither (36·4%; 95% CI: 36·4-36·4%). Interpretation: Community treatment facilities should be supported to provide medications for OUD and accommodate rising rates of methamphetamine and polysubstance-related treatment admissions in populations experiencing complex social drivers of health such as homelessness, CJI, or both. Funding: National Institute of General Medical Sciences and National Institute of Diabetes and Digestive and Kidney Diseases.